2013
DOI: 10.1007/s00018-013-1413-2
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous translocation and intracellular trafficking of the cell-penetrating and immune-suppressive effector protein YopM

Abstract: Extracellular Gram-negative pathogenic bacteria target essential cytoplasmic processes of eukaryotic cells by using effector protein delivery systems such as the type III secretion system (T3SS). These secretion systems directly inject effector proteins into the host cell cytoplasm. Among the T3SS-dependent Yop proteins of pathogenic Yersinia, the function of the effector protein YopM remains enigmatic. In a recent study, we demonstrated that recombinant YopM from Yersinia enterocolitica enters host cells auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 36 publications
1
35
0
Order By: Relevance
“…These data suggest that ␣1H and ␣2H employ direct translocation as an alternative or even parallel uptake mechanism to enter HeLa cells. This is in accordance with our previous findings for full-length YopM which primarily enters cells by endocytosis but also employs direct membrane penetration as an entry mechanism (28,29). In contrast, Tat uptake was completely inhibited at 4°C in HeLa cells, suggesting that direct translocation of Tat can be excluded in this cell line.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These data suggest that ␣1H and ␣2H employ direct translocation as an alternative or even parallel uptake mechanism to enter HeLa cells. This is in accordance with our previous findings for full-length YopM which primarily enters cells by endocytosis but also employs direct membrane penetration as an entry mechanism (28,29). In contrast, Tat uptake was completely inhibited at 4°C in HeLa cells, suggesting that direct translocation of Tat can be excluded in this cell line.…”
Section: Discussionsupporting
confidence: 93%
“…In particular, two CPPs derived from the Y. enterocolitica effector protein YopM were employed and their functional properties were characterized. We had previously shown that the Y. enterocolitica-derived YopM protein can autonomously translocate into eukaryotic cells independently of the T3SS (28)(29)(30). Autonomously cell-penetrating recombinant YopM is functional and downregulates the expression of proinflammatory cytokines (4,34), suggesting a dual use of YopM as a delivery vehicle for cargo molecules and as a biological therapeutic for immunomodulation (31,32).…”
mentioning
confidence: 99%
“…Therefore, the lack of coexpression of the genes with yopM does not exclude possible translocation of the LRR proteins through the Ysa T3SS. Alternatively, the LRR proteins may also enter host cells and act as effectors by other secretion mechanisms, such as autotranslocation (10). The LRR genes were not detected in the chromosomes of all Yersinia species, possibly due to acquisition of the ancestral genes after species diversification had occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Boland et al sequenced a homologous yopM gene from Y. enterocolitica strain W22703 and demonstrated that the N-terminal 100 residues gave YopM the ability to translocate into the host cell cytoplasm through the Ysc type III secretion system (T3SS) (8). YopM also showed the ability to enter the host cell cytoplasm by autonomous translocation independently of T3SSs (9,10). In another study, YopM-specific antibodies did not slow the progression of experimental plague, indicating that YopM may have a major intracellular function (11).…”
mentioning
confidence: 99%
See 1 more Smart Citation